COVID-19 vaccine acceptability among healthcare workers in Yemen - Abdullah A. Al-Mikhlafy; Mahdi Al Karawani; Rashad Abdul-Ghani; Ibrahim Alsubol; Asmaa A. H. Al-Awadi; Mogahid Y. Nassar; Mohammed A. Alshehab; Adel Almutawakel; Adeeb Salah; Ahlam A. Abdultwab (WHO Regional Office for the Eastern Mediterranean (WHO/EMRO), 2023)
Background: Acceptability of COVID-19 vaccine by healthcare workers (HCWs) can affect its acceptability by the general population. Aim: To assess COVD-19 vaccine acceptability among HCWs in Sana'a, Yemen. Methods: We conducted a multicentre cross-sectional study among 391 HCWs in Sana'a, Yemen, from January to March 2022. We used a self-administered questionnaire to collect data on the demographics, profession, academic qualifications, and experience of HCWs, as well as their COVID-19 vaccine acceptability or hesitancy. We used univariate and multivariable logistic regression to analyse the association between the independent variables and vaccine hesitancy (P < 0.05). Results: Of the 391 HCWs, only 194 (49.6%) were willing to accept the COVID-19 vaccine. The most frequent reasons for vaccine hesitancy were fear of adverse reactions (77.7%), concerns about unknown effects of the vaccine in the future (73.1%), and uncertainty about the safety of new vaccines (69.5%). Female gender and working in the public sector were independent predictors of vaccine hesitancy among the HCWs. Conclusion: Nearly half of the HCWs in Sana'a, Yemen, were willing to accept the COVID-19 vaccine. Female gender and working in the public health sector were independent predictors of vaccine hesitancy. We recommend further studies to compare COVID-19 acceptability among HCWs in the public and private sectors in Yemen.